Activities of Ambassadors of Health and Sports - An Effective Way to Protect the Health of the Population - Sharipova Dilara Djumaniyazovna; Yaqubova Dono Bahodirovna (Researchparks Publishing, 2022)
A national policy in which physical activity has a central place may foster the implementation of a national physical activity plan. This should include a formal statement that defines physical activity as a priority area, states specific goals and provides a strategic plan for action. A policy on physical activity may be a stand alone document or be integrated within policies addressing the prevention and control of noncommunicable disease, or health promotion.